2021
DOI: 10.1186/s12917-021-02990-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of myrislignan levels in BALB/c mouse plasma by LC-MS/MS and a comparison of its pharmacokinetics after oral and intraperitoneal administration

Abstract: Background Myrislignan is a natural product from Myristica sp. with diverse pharmacological activities. Recently, the anti-Toxoplasma gondii (T. gondii) activity of myrislignan has been proposed, and in vivo studies of its pharmacokinetics in BALB/c mice are necessary to further evaluate the clinical effects of myrislignan. Results In this study, a sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed and validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Myrislignan is a lignan isolated from Myristica fragrans Houtt with diverse pharmacological activities [ 13 ]. It can be metabolized by liver CYP450 enzymes and penetrate the blood-brain barrier through passive diffusion [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Myrislignan is a lignan isolated from Myristica fragrans Houtt with diverse pharmacological activities [ 13 ]. It can be metabolized by liver CYP450 enzymes and penetrate the blood-brain barrier through passive diffusion [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is need to identify potential target genes and develop effective targeted drugs to improve the outcomes of glioma patients. Myrislignan is a lignan isolated from Myristica fragrans Houtt with diverse pharmacological activities [13]. It can be metabolized by liver CYP450 enzymes and penetrate the blood-brain barrier through passive diffusion [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have the advantage of availability, low manufacturing cost, and lack of adverse effects, which has been an essential source of developing new medicine gradually (22,38). In searching for a new bioactive natural treatment with anti-osteoclast formation, we found that MRL functioned as anti-in ammation, anti-cancer, and anti-mitochondria (32,33,47). However, MRL's speci c mechanisms of action in osteoclast formation and mitochondrial function have yet to be investigated deeply.…”
Section: Discussionmentioning
confidence: 99%
“…The stability was evaluated by analyzing repeats ( n = 6) of QC samples with concentrations of 15 ng·mL −1 , 400 ng·mL −1 and 4000 ng·mL −1 under different sample storage and processing procedures: (1) plasma samples were kept at ambient temperature for 24 h (2) plasma samples were stored at -20 °C for 60 days (3) plasma samples were stored in an autosampler at 4 °C for 24 h (4) plasma samples were measured after three freeze–thaw cycles (25 °C to -20 °C) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%